Estudo de utilização de uma minimum spanning tree de correlações como seletora de ações em uma estratégia de cointegração no mercado brasileiro - Tomaz, Felipe Rodrigues de Menezes (2017)
This work aimed to evaluate the possibility of using a miminum spanning tree (MST) of correlation between assets as a selection tool in a pairs trading strategy based on cointegration. From a selection of Bovespa exchange index assets, cointegration tests were performed between pairs of assets and, subsequently, starting from positive results, backtestings were executed. After that, the backtestings were filtered by information included in an MST. For a given period, when a cointegration was found between a pair of assets, a MST was developed and it was analyzed if there was a direct link between those assets in the MST’s structure. Otherwise, the backtesting result from the cointegration would be disregarded. By comparing the total set of results with the subset of results that took into account the MST constraint, it was evaluated the impact of the use of the MST, as an asset selector, on the result of the pairs trading strategy.